(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
Oleic acid is a fatty acid known as omega-9, which is found naturally in many plant sources and animal products and is found in the form of tri-glycerides (oleic acid esters). In this research, the oleic acid was isolated and purified with a high degree of purity up to 99% of the fatty acids extracted from olive oil, corn oil and palm oil with a yield of at least 87% of its percentage in the oils used by the use of crystalline urea as well as crystalline selective cooling . GC-FID was also used for direct quantitative analysis of oleic acid and other fatty acids.